Penerapan Inhalasi Sederhana menggunakan Daun Mint terhadap Ketidakbersihan Jalan Nafas pada Keluarga Ny.A dengan TB Paru - Rismayanti Maimunah; Rachmawati, Kurnia (School of Nursing, Faculty of Medicine and Health Science, Lambung Mangkurat University., 2023)
TB is an infectious disease caused by the bacterium Mycobacterium tuberculosis that attacks the lungs and other organs. One of the symptoms of pulmonary TB is shortness of breath. Shortness of breath is a real symptom of tracheobronchial disorders, lung parenchyma and pleural cavities.